The Potential of Gold Nanobipyramids as Anti-Fungal for Dermatophytes Fungi at Living Animals - Wing Kang Khor; Marlia Morsin; Nur Liyana Razali (Emerging Advances in Integrated Technology, 2024)
Dermatophytes are a group of fungi that cause dermatophytosis, a type of skin infection affecting both humans and animals. While dermatophytosis is typically self-limiting, it can pose significant challenges for individuals with weakened immune systems. Additionally, current treatment options for dermatophytosis have their limitations, including issues of toxicity, inefficacy, and the emergence of drug-resistant strains. Recently, nanotechnology-based approaches have emerged as a promising strategy to overcome the drawbacks of conventional antifungal medications. Gold Nanoparticles (GNPs) have demonstrated substantial antifungal activity against various fungal species, including dermatophytes. Among these, Gold Nanobipyramids (GNBPs) exhibit unique physicochemical properties that enhance their effectiveness against dermatophytes. Gold Nanobipyramids (GNBPs) were synthesized using the Seed-Mediated Growth Method (SMGM) due to its simplicity. Optically, GNBPs displayed plasmonic peaks at 1.548 (wavelength 561 nm) and 2.372 (wavelength 807 nm). Structurally, intensity peaks at 38.15° (plane 111) and 44.49° (plane 200) were identified. GNBPs has surface density ~70.227±0.530. In the dermatophyte treatment process, GNBPs exhibited varying inhibitory effects. At 40% concentration, fungal growth persisted, with surface density similar to the no control area. At 60%, inhibition occurred, though less efficiently. The most effective inhibition was observed at 80%, and complete inhibition was achieved at 100% concentration. GNBPs proved successful in inhibiting fungal growth, attributed to their curvature and sharp edges interacting with microbial cell membranes, leading to membrane damage and cellular content leakage.